(untitled) (Web of Teachers: Inderscience Research, 2025)
This article provides general information about the scientific foundations, methodology, and practical methods of training young basketball players and leading them to achieve high results in sports. The process of teaching basketball is not limited to developing technical skills but also requires collaboration across fields such as physics, psychology, pedagogy, and medicine. The article examines issues related to the individual characteristics of young basketball players, their physical and mental state, as well as the effectiveness of training systems and processes. Based on the knowledge and experiences focused on young athletes, the article analyzes methodological guidelines and the scientific-psychological aspects of development. Additionally, it includes suggestions and recommendations that can be applied in practice.